If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -5) + -7(y) = -15 Reorder the terms: 2(-5 + y) + -7(y) = -15 (-5 * 2 + y * 2) + -7(y) = -15 (-10 + 2y) + -7(y) = -15 Combine like terms: 2y + -7y = -5y -10 + -5y = -15 Solving -10 + -5y = -15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -5y = -15 + 10 Combine like terms: -10 + 10 = 0 0 + -5y = -15 + 10 -5y = -15 + 10 Combine like terms: -15 + 10 = -5 -5y = -5 Divide each side by '-5'. y = 1 Simplifying y = 1
| 3(n+10)+11=7n-1 | | 5(b-1)+3(b-1)=4(3-b)+3(4b-2) | | 6(1-2n)=(-3)(n-2) | | x+x+(4*x)+90=180 | | -2-(4-3x)=-7 | | x+x+(4*x)+90=360 | | (-2x-1/3x)×(-9/7x^3y) | | 5x+2.5x+1=55 | | 6(1-2n)=-3(n-2) | | 8x+10x^2-6=17x | | 1-6(2x-3)=-2 | | 5-2(x+2)=9 | | 15x^5+11x^3-14x=0 | | 2x=-32-5(4x-2) | | 5-3(x+2)=9 | | 6(1-2n)=-2(n-2) | | x=y+1-4 | | (9x-8)+(10x+10)= | | Y=x+1-4 | | 4x^2-6x-10-mx-m=0 | | 2.5+10=1.5+17 | | 5x-2(2x+2)=-6 | | 9b-4=1+6(b+11) | | sqrt(6+x)*sqrt(4-x)=3 | | 10+-2z=-30 | | 11x-5=60 | | 5m-4=3m+12 | | w^3+5w^2+-23w-3= | | -2=-9-2(-2x+1) | | -7f+-31=53 | | X^3-2x+21=0 | | 20+-10c=100 |